Clinical potential of the Hippo-YAP pathway in bladder cancer - Cheng, Xin; Lou, Kecheng; Ding, Liang; Zou, Xiaofeng; Huang, Ruohui; Xu, Gang; Zou, Junrong; Zhang, Guoxi (Frontiers in Oncology, 2022)
Bladder cancer (BC) is one of the world’s most frequent cancers. Surgery coupled with adjuvant platinum-based chemotherapy is the current standard of therapy for BC. However, a high proportion of patients progressed to chemotherapy-resistant or even neoplasm recurrence. Hence, identifying novel treatment targets is critical for clinical treatment. Current studies indicated that the Hippo-YAP pathway plays a crucial in regulating the survival of cancer stem cells (CSCs), which is related to the progression and reoccurrence of a variety of cancers. In this review, we summarize the evidence that Hippo-YAP mediates the occurrence, progression and chemotherapy resistance in BC, as well as the role of the Hippo-YAP pathway in regulating bladder cancer stem-like cells (BCSCs). Finally, the clinical potential of Hippo-YAP in the treatment of BC was prospected.